The treasure in the garden - McKay, Hilary; Kenyon, Tony (Hodder Children's London, 1998)
Join Danny, Nathan and Anna, the children of Paradise House, in another mischievous adventure. This time, they help Nathan solve a secret about a boy who lived in their house long ago.